Cross-Reactivity of Schistosoma mansoni Cytosolic Superoxide Dismutase, a Protective Vaccine Candidate, with Host Superoxide Dismutase and Identification of Parasite-Specific B Epitopes - Carvalho-Queiroz, Claudia (American Society for Microbiology, 2004)
Schistosoma mansoni, an intravascular parasite, has evolved a number of immune evasion mechanisms to establish itself in the host, such as antioxidant enzymes. Our laboratory has demonstrated that the highest levels of certain antioxidant enzymes are found in adult worms, which are the least susceptible to immune killing. Vaccination of mice with naked DNA constructs containing the gene encoding Cu/Zn cytosolic superoxide dismutase (SmCT-SOD) showed significant levels of protection compared to a control group, and our data demonstrate that the adult worms are a target of the immune response that confers resistance in SmCT-SOD DNA-vaccinated mice. Because SmCT-SOD shows significant identity with the human homologue, we evaluated the reactivity of anti-SmCT-SOD antibodies derived from SmCT-SOD-immunized mice and rabbits and from S. mansoni-infected individuals to human superoxide dismutase (hSOD) and SmCT-SOD parasite-specific peptides to assess the potential for autoimmune responses from immunization with the recombinant molecule. In addition, we evaluated the ability of various SmCT-SOD adjuvant-delivered immunizations to induce cross-reactive antibodies. Both mouse and rabbit antibodies generated against SmCT-SOD recognized the denatured form of hSOD. The same antibodies did not recognize nondenatured hSOD. Sera from infected individuals with different clinical forms of schistosomiasis recognized SmCT-SOD but not hSOD. Antibodies from mice immunized with different SmCT-SOD-containing formulations of both DNA and protein were able to recognize SmCT-SOD-derived peptides but not soluble hSOD. All together, these findings serve as a basis for developing a subunit vaccine against schistosomiasis.